Manajemen Penanaman Nilai-Nilai Agama Islam pada Siswa Taman Kanak-Kanak Tunas Harapan di Sambiroto Gajah Demak - Mustakimah Mustakimah; Fatah Syukur (Universitas Islam Negeri Walisongo, 2021)
This reseach aims to determine the process of inculcating Islamic religious values in Tunas Harapan Sambiroto Kindergarten students, the methods used in instilling Islamic religious values, and the results of using the method of inculcating religious values. The results showed that: in an effort to instill religious values in TK Tunas Harapan Sambiroto students, various planting methods were combined. As a supporting factor, educators have high motivation, have the ability to convey Islamic religious teachings, students can imitate worship movements even though they are not regular and have Islamic books. Meanwhile, factor for students not focusing and grouping participants what educators do when practicing worship is still unclear